Graphene-MoS2 nanosheet composites as electrodes for dye sensitised solar cells. (7th March 2016) - Lynch, Peter; Khan, Umar; Harvey, Andrew; Ahmed, Iftikhar; Coleman, Jonathan N
Abstract: Replacing the platinum counter electrode in dye-senstized solar cells with a cheaper material has attracted much attention recently. Graphene, graphene oxide and other 2-dimensional materials have received significant attention. Here we demonstrate the dependence of device parameters on the thickness of counter electrodes formed from porous, disordered arrays of liquid-exfoliated graphene nanosheets. We find device efficiency to saturate at a counter electrode thickness of ∼400 nm. Such optimised counter electrodes can be improved further by adding MoS2 nanosheets to the graphene electrode. By measuring the dependence of device parameters on the composition of mixed graphene/MoS2 electrodes, we show that adding ∼10 wt% MoS2 nanosheets to a graphene counter electrode improves performance and can result in a cell efficiency of ∼95% of that achieved using a platinum electrode. This data is consistent with the MoS2 nanosheets being somewhat better catalysts than the graphene nanosheets. However, the graphene nanosheets are required to render the electrode conductive. More detailed analysis suggests the better performance of the MoS2 nanosheets to be mostly down to their smaller size.